Factors That Pose Challenges For MSMEs in Engaging With The Government Procurement Digital Marketplace - Devi Yanurida; Ratri Istania; Asropi Asropi (Yayasan Riset dan Pengembangan Intelektual, 2023)
Procurement of government goods and services is a very important activity in realizing development. Due to changes in conditions to save the National Economy, the government issued Presidential Instruction number 2 of 2022. LKPP responded by issuing a new policy to make it easier to spend on government procurement of goods/services with a focus on using micro, small and medium enterprise products. However, this policy has not had an impact on increasing the number of MSME providers and products in the Government Procurement Digital Market. Therefore, this article tries to analyze the factors that pose challenges for MSMEs in their involvement in the Government Procurement Digital Market. Study of the factors that pose challenges for MSMEs in involvement in the Government Procurement Digital Market using quantitative methods. Factors that pose challenges for the involvement of MSMEs in the Government Digital Procurement Market include: Policy Complexity, Available Resources, Involvement of Implementers and Interest Groups in the planning process, Consistency between Policy and Organizational Values, Leadership and Political Support, Openness Inter-Organizational Communication, Dependence on External Resources, Dependence on Technology & Human Resources, Dependence on Other Institutions.